БИТКОИН И КЛАУЗУЛЕ КРИПТОВАЛУТЕ - Srdjan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Nowadays, it is almost impossible to imagine an effective legal system that is not somehow inspired by nominalistic ideas. However, the principle of monetary nominalism is not necessary in correlation with other higher principles, like the principle of fairness, for example. So, legislators build and implement corrective instruments in legal acts, most of the time allowing legal subjects to choose and adapt those instruments to best fit their economic interests. In that context, probably the most frequently used instrument is (foreign) currency clauses. Those norms, when implemented in contract, prevent negative effects of domestic currency depreciation through the denomination of the amount of debt in foreign currency. Whether we think of them as a currency or not, cryptocurrencies are becoming a more important part of our digitized economic world. So, unless the legislature strictly limits freedom of the will in contract law by banning cryptocurrencies, parties can hedge against domestic currency depreciation by pegging the amount of debt to the exchange rate of one of thousands of existing cryptocurrencies. If parties choose to make such an agreement, it is most likely that they will peg the amount of debt to the exchange rate of bitcoin. Legal system of the Republic of Serbia does not regulate cryptocurrencies, which means that it does not ban them. So, in this paper, we analyze (crypto)currency clauses nominated in bitcoin and their effects on contract relations in the legal system of the Republic of Serbia. In this research, we heavily rely on advantages of normative and comparative methods and various techniques of the analytical method.